2006
DOI: 10.1111/j.1365-2788.2006.00880.x
|View full text |Cite
|
Sign up to set email alerts
|

Deletions of VCX‐A and NLGN4: a variable phenotype including normal intellect

Abstract: These findings suggest that deletion of VCX-A and NLGN4 can result in variable phenotypic features and that normal mental development can be achieved despite this deletion, emphasizing the importance of environmental factors and possible modifier genes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
46
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 16 publications
2
46
0
2
Order By: Relevance
“…This is further supported by the finding of point mutations in NLGN4X in related males with X-linked mental retardation and autism (Laumonnier et al, 2004) and in siblings with autism (Jamain et al, 2003). However, one family with a deletion of STS, VCXA and NLGN4 showed variable phenotype amongst the three affected males (Macarov et al, 2007).…”
Section: Introductionmentioning
confidence: 63%
See 1 more Smart Citation
“…This is further supported by the finding of point mutations in NLGN4X in related males with X-linked mental retardation and autism (Laumonnier et al, 2004) and in siblings with autism (Jamain et al, 2003). However, one family with a deletion of STS, VCXA and NLGN4 showed variable phenotype amongst the three affected males (Macarov et al, 2007).…”
Section: Introductionmentioning
confidence: 63%
“…As in previous studies (Aviram-Goldring et al, 2000;Cuevas-Covarrubias and Gonzalez-Huerta, 2008;Kent et al, 2008), we confirmed that the presence of marker DXS996 in patients with STS deficiency is predictive of normal development. In contrast, in the literature, a number, though not all, of patients who are deleted for DXS996 have been reported to present with developmental delay and some meet the diagnostic criteria for autism spectrum disorder (Macarov et al, 2007;Kent et al, 2008). This provides support for including DXS996, or other markers that map at the NLGN4 locus, in the panel of markers to be typed in any prenatal case found to have an STS deletion.…”
Section: Molecular Analysismentioning
confidence: 99%
“…This would result in various different clinical manifestations that might be quite atypical, but jointly might also be able to cause autism-like features, which is supported by reports on Xp22.3 deletions, in which patients show the variable association of apparently unrelated clinical manifestations. 37,38 Jointly, the multiple genes with their resulting clinical phenotypes could increase the probability of developing autism. Additional support for autism as a partly contiguous gene syndrome, and the probable existence of different subtypes, comes from CNV studies identifying rare variants covering multiple genes of different function in the etiology of autism.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genetic changes in Nrxn [84][85][86][87][88][89][90][91][92][93][94] and Nlgn genes [92,93,[95][96][97][98][99][100][101][102][103][104][105][106][107][108][109][110] have been found in ASD patients. These changes include (i) point mutations, which cause frame shifts, small deletions, and missense mutations in both coding and promoter regions, (ii) distinct translocation events, and (iii) large-scale deletions of chromosomal DNA containing these gene loci.…”
Section: Neurexins and Neuroliginsmentioning
confidence: 99%